The Influence of Elementary School Principal’s Supervision on the Implementation of Merdeka Curriculum in the Digital Era: Systematic Literature Review - Marini, Marini (PPSDP International Journal of Education, 2025)
This study aims to analyze the influence of elementary school principal supervision in Jejawi District on the implementation of Merdeka Curriculum in the digitalization era. In the era of digital transformation, principals have a strategic role as supervisors to ensure that teachers are able to adapt to curriculum changes by utilizing technology. This study uses a quantitative approach with a survey method, involving 50 teachers from 10 elementary schools in Jejawi District as respondents. Data were collected through a questionnaire covering aspects of academic, technical, and professional development supervision. The results of the study showed that principal supervision had a significant effect on the success of Merdeka Curriculum implementation. The aspect of academic supervision had the most dominant influence followed by technical supervision and professional development. These findings indicate that principals need to optimize technology-based supervision and collaboration to support teachers in facing the challenges of the digital era. This study recommends improving principal competence in digital-based supervision to support the sustainability of Merdeka Curriculum implementation.